2021
DOI: 10.1111/zph.12853
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni ST50, a pathogen of global importance: A comparative genomic analysis of isolates from Australia, Europe and North America

Abstract: Campylobacter jejuni is the leading cause of bacterial gastroenteritis globally, and infections are often transmitted through consumption of raw or undercooked poultry.Campylobacter jejuni ST50 is among the top ten sequence types (STs) reported in the collected isolates listed at PubMLST records from poultry, food and clinical sources for Asia, Europe, North America, Oceania and South America. This study was designed to determine the most commonly reported C. jejuni STs globally using the PubMLST database and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 52 publications
6
15
0
Order By: Relevance
“…It was the second most common ST in North America and the sixth most common ST in South America. This sequence type has been recently characterized in C. jejuni genomes from North America, Europe, and Australia, highlighting its importance as a global pathogen [16]. The ST50 distribution presented here corroborates with Wallace et al [16], who showed that the ST50 is among the top ten commonly reported STs within the more than 77,000 sequences deposited in the PubMLST in all continents except Africa.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was the second most common ST in North America and the sixth most common ST in South America. This sequence type has been recently characterized in C. jejuni genomes from North America, Europe, and Australia, highlighting its importance as a global pathogen [16]. The ST50 distribution presented here corroborates with Wallace et al [16], who showed that the ST50 is among the top ten commonly reported STs within the more than 77,000 sequences deposited in the PubMLST in all continents except Africa.…”
Section: Discussionsupporting
confidence: 88%
“…This sequence type has been recently characterized in C. jejuni genomes from North America, Europe, and Australia, highlighting its importance as a global pathogen [16]. The ST50 distribution presented here corroborates with Wallace et al [16], who showed that the ST50 is among the top ten commonly reported STs within the more than 77,000 sequences deposited in the PubMLST in all continents except Africa. Interestingly, none of the host generalist sequence types ST21, ST45, and ST48 were reported top in Africa, Asia, and South America, although the chicken specialist ST353 [38][39][40] was most frequently identified in Africa and South America.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Geographical differences have been noted in ST-21 CC [41,78,[110][111][112][113]. ST-21 CC isolates are among the most common C. jejuni genotypes isolated worldwide, with one quarter of C. jejuni isolates recorded in the pubMLST database are ST-21 CC.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical differences have been noted in ST-21CC (Kärenlampi et al, 2007;Kovanen et al, 2014;Olkkola et al, 2016;Pascoe et al, 2017;Wallace et al, 2021). ST-21 CC isolates are among the most common C. jejuni genotypes isolated worldwide, with one quarter of C. jejuni isolates recorded in the pubMLST database are ST21 CC.…”
Section: Antimicrobial Resistance Genes Are Distributed Across Isolatesmentioning
confidence: 99%